Edu-Spirituality Building: Environmental Awareness Through Njogo Resan - Hidayah Binsa, Ucik (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to determine the implementation of planting and maintaining protective trees (Njogo Resan) as a means of conveying environmental messages that have an impact on students' spiritual education at MIS NU Abu Bakar Bancangan, Sambit, Ponorogo. This type of research is Qualitative with a case study approach at MIS NU Abu Bakar Bancangan, Sambit, Ponorogo. The subjects of this research are students, scout coaches, and teachers. Data collection methods through observation, interviews, and documentation. Data analysis was carried out by following the interactive model of Miles Huberman with several stages, namely data collection, data reduction, data presentation, and conclusion drawing. Based on the results of observations, interviews, and documentation, it shows that the implementation of Njogo Resan activities, namely scout coaches invite students to plant protective tree / Resan seeds with the characteristics of their roots that can absorb a lot of water on Widodaren hill because the location is a victim of burning to open agricultural land for residents, and maintain it by watering it regularly. The impact of Njogo Resan on the Spiritual education of students was successfully embedded, namely establishing good relations with fellow creatures created by Allah SWT (Hablu min al-Nās), which includes humans, animals, and plants in the surrounding environment.